2017
DOI: 10.15406/jpcpy.2017.07.00447
|View full text |Cite
|
Sign up to set email alerts
|

Young Adults’ Attitudes towards Rape and Rape Victims: Effects of Gender and Social Category

Abstract: Violence against women, especially rapes, has been a pervasive problem in the society. It is well documented that victims of rape not only experience serious short and longterm psychological harm as a direct result of the assault, but may also be stigmatized by others (e.g., be blamed for not resisting enough). While there are sufficient studies in the developed countries that have examined how various gender and other ideologies relate to prejudiced attitudes toward rape victims, much less work has been done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Adherence to such normative beliefs spells negative effects on sexual health (Álvarez-Muelas et al, 2020;Grose et al, 2014;Sánchez et al, 2005). Man-favorable SDS is related to favorable attitudes toward raping women (Jamshed & Kamal, 2019;Lee et al, 2010;Mittal et al, 2017;Moyano et al, 2017;Sierra, Costa et al, 2009;Wanfield, 2018), by constituting a predictor of such attitudes . It has also been associated with aggressive sexual behavior to women (Moyano et al, 2017;Russell & Oswald, 2001;Teitelman et al, 2013;Zurbriggen, 2000), by predicting male sexual coercion toward females (Sierra, Gutiérrez-Quintanilla, et al, 2009), female sexual victimization (Dunn et al, 2014;Koon-Magnin & Ruback, 2012;Lee et al, 2010;, and sexual violence recognition being more difficult (Kim et al, 2019).…”
Section: Article In Pressmentioning
confidence: 99%
“…Adherence to such normative beliefs spells negative effects on sexual health (Álvarez-Muelas et al, 2020;Grose et al, 2014;Sánchez et al, 2005). Man-favorable SDS is related to favorable attitudes toward raping women (Jamshed & Kamal, 2019;Lee et al, 2010;Mittal et al, 2017;Moyano et al, 2017;Sierra, Costa et al, 2009;Wanfield, 2018), by constituting a predictor of such attitudes . It has also been associated with aggressive sexual behavior to women (Moyano et al, 2017;Russell & Oswald, 2001;Teitelman et al, 2013;Zurbriggen, 2000), by predicting male sexual coercion toward females (Sierra, Gutiérrez-Quintanilla, et al, 2009), female sexual victimization (Dunn et al, 2014;Koon-Magnin & Ruback, 2012;Lee et al, 2010;, and sexual violence recognition being more difficult (Kim et al, 2019).…”
Section: Article In Pressmentioning
confidence: 99%
“…Similarly, no group differences were recorded for alcohol-related RMA between male perpetrators and non-perpetrators, suggesting that alcohol-related RMA is similar among men, regardless of perpetrator status. The significant difference between male and female perpetrators and male and female non-perpetrators in terms of RMA seems to reflect a general tendency for men to adhere more prominently to attitudes supportive of sexual coercion (Mittal et al, 2017).…”
Section: Group Comparisonsmentioning
confidence: 88%
“…Several empirical studies examined factors that influence rape myths acceptance among the population (Buddie & Miller, 2001;Burt, 1980;Chapleau, Oswald, & Russell, 2008;Ching & Burke, 1999;Cowan, Campbell & Robin, 1995;Johnson, Kuck, & Schander, 1997;Mittal et al, 2017;Lonsway & Fitzgerald, 1994;Pierson, 2016). These studies have collectively found numerous variables that influence citizens' acceptance of rape myths.…”
Section: Sexual Violence Rape Myths and Attitudes: A Reviewmentioning
confidence: 99%